OX40 signaling in cancer immunotherapy: mechanisms of action, translational applications, and therapeutic perspectives - Luo, Yuehua; Li, Jing; Li, Le; Qin, Bingbing; Zhou, Ruisheng; Tang, Ying (Frontiers in Immunology, 2026)
OX40 (CD134/TNFRSF4), a costimulatory receptor of the TNF receptor superfamily ((TNFRSF), has emerged as a compelling immuno-oncology target given its capacity to amplify T-cell activation, sustain effector and memory responses, and remodel the tumor microenvironment (TME). This review provides a comprehensive synthesis of OX40 biology from molecular architecture to pathway-specific signaling programs, emphasizing its distinct yet interconnected roles across CD4+ T-cell subsets, CD8+ T cells, T follicular helper cells, and regulatory T cells (Tregs). We further summarize the landscape of OX40 expression across major solid tumors, highlighting its heterogeneous prognostic significance and the immune-contextual factors that determine therapeutic responsiveness. Although early-phase clinical studies of OX40 agonists have demonstrated favorable tolerability and robust pharmacodynamic activation, their antitumor efficacy either as monotherapy or in combination with PD-1/PD-L1 or CTLA-4 inhibitors has remained modest. Mechanistic barriers such as transient OX40 expression kinetics, Treg counteractivation, metabolic suppression, and insufficient FcγR-mediated crosslinking likely underlie this translational gap. Emerging bispecific antibody platforms and OX40-integrated combinatorial regimens offer renewed opportunities to overcome these limitations by enabling spatially controlled receptor clustering, TME-selective activation, and multi-pathway synergy. Future translational success will require refined dosing strategies, optimized antibody engineering, biomarker-guided patient selection, and integrated approaches that align OX40 activation with favorable immune dynamics in the TME.